Hormonal Changes in Response to Different Chemicals Induced Flowering and Improved Fruit Yield in Pomegranate cv. Bhagwa - Firoz Hussain, S.; Upreti, K.K.; Laxman, R.H.; Murthy, B.N.S.; Satisha, J.; Ramaiah, Muniam; Vidya Rani, N. (Annals of Arid Zone, 2023)
At the ICAR-Indian Institute of Horticultural Research (IIHR), Hesaraghatta, Bengaluru, a field study was carried out to elucidate the impact of different propagules, chemicals, and their interactions on induction of flowering, improving fruit yield, and endogenous phytohormones (Gibberellins and Indole 3 Acetic Acid) in different propagules (tissue culture plants, grafted plants, and air layer plants) of pomegranate (Punica granatum). The effects of three chemicals, methyl jasmonate (100 ppm, 150 ppm, and 200 ppm plant-1), nitrobenzene (1.0, 1.5, and 2.0 ml plant-1), and paclobutrazol (0.375 g a.i. m-1 canopy diameter), applied 30, 45, and 60 days after withholding irrigation (bahar treatment) on all three propagules, were studied. During ambe and hastha bahar, tissue culture plants (P1) produced the most hermaphrodite flowers (261.6, 233.2) and fruit yield (32.88 kg plant-1, 35.57 kg plant-1) among the propagules. In the instance of ambe bahar, soil drenching of paclobutrazol 0.375 g a.i. m-1 canopy diameter 60 days after bahar treatment (T9) resulted in the most hermaphrodite flowers (267.3) and fruit yield (30.54 kg plant-1). In the instance of hastha bahar, foliar spraying with nitrobenzene 2.0 ml L-1 plant-1 (T6) resulted in a high number of hermaphrodite flowers (253.8) and fruit yield (48.19 kg plant-1). In the case of ambe bahar, tissue culture plants (P1) produced considerably more hermaphrodite flowers (335.3) and fruit production (30.54 kg plant-1) than other interactions. Application of nitrobenzene 2.0 ml L-1 plant-1 (T6) to tissue culture plants (P1) during hastha bahar resulted in the formation of 275.2 hermaphrodite flowers and the highest fruit yield (51.44 kg plant-1). The leaves of tissue culture plants (P1) showed decreased endogenous gibberellin levels and greater Indole 3 Acetic Acid levels during the blooming and fruit set stages of ambe bahar and hastha bahar. Paclobutrazol 0.375 g a.i. m-1 canopy diameter soil drenching 60 days after bahar treatment (T9) resulted with reduced endogenous gibberellin levels and greater Indole 3 Acetic Acid levels among the chemicals.